SYSTEMATIC INNOVATIVE DIAGNOSTICS (SID) - Náhlik, Gábor (Periodica Polytechnica Mechanical Engineering, 1986)
Main aim of Systematic Innovative Diagnostics (SID) is to find a common functional basis for solving the engineering control and organizational problems in production systems. Its application is justified when designing reconstructions, developing new production systems, introducing additional automation or just the application of microprocessors. In the development phase of SID-where hundreds of students took part-some methods of filmtechnics, of collective intellectual creative technics, of functional analysis and those of collective decision making have been put into one single, unified system. It has been assumed, that a visual preparation before using collective creative methods results in such an excess outcome, which shortens considerably the innovative processes in production systems compared to traditional methods and-at the same time-integrates organizational and technical design. The process of SID application is shown together with experiments for proving the input assumption. A practical example illustrates the introduced method.